Automatic Iranian Vehicle License Plate Recognition System Based on Support Vector Machine (SVM) Algorithms - Mahdi Aghaie; Fatemeh Shokri; Meisam Yadolah Zade Tabari (Computer Engineering and Applications Journal, 2013)
There are far more cars on the road now than there used to be. Therefore, Controlling and managing the huge volume of traffic is virtually impossible without the use of computer technology. This paper represents design and implement of an intelligent system for license plate recognition based on three main steps. This process includes the detection of license plate location, character segmentation and character recognition. In this study, we used Classifier svm to detect the characters. According to the results, the performance of the proposed system is better compared to similar algorithms such as neural network. It is worth mentioning that Recognition Approach is tested in various conditions and results are described. Â  Keyword- Vehicle license plate recognition, Morphology Operations, Histogram, The edge detection, Classifier SVMDOI:Â 10.18495/comengapp.21.161174